Re-description of Clubiona huaban (Araneae, Clubionidae), with the first description of the female - Jianshuang Zhang; Qiwen Du; Yingchen Dai; Hao Yu (Biodiversity Data Journal)
Clubiona huaban Xin, Zhang, Li, Zeng & Yu, 2020, one of the members of the Clubiona trivialis group, was described, based on two male types from Xiangzhigou Scenic Spot, Guyang City, Guizhou Province, China.Recently, new material of sac spiders has been collected from southwest China, including the type locality. The males were identified as C. huaban, based on comparison with the holotype. On the basis of the morphological characters and DNA barcoding, we credibly matched the females and males together as C. huaban. Therefore, C. huaban is re-described, based on new material and the female is described and illustrated for the first time.